2022
DOI: 10.1186/s12889-022-13438-9
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of socioeconomic inequalities in preterm birth: a systematic review

Abstract: Background Rates of preterm birth are substantial with significant inequalities. Understanding the role of risk factors on the pathway from maternal socioeconomic status (SES) to preterm birth can help inform interventions and policy. This study therefore aimed to identify mediators of the relationship between maternal SES and preterm birth, assess the strength of evidence, and evaluate the quality of methods used to assess mediation. Methods Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 85 publications
2
29
0
Order By: Relevance
“…The factors affecting preterm births are many, including medical causes. 46,47 In addition, economic and social factors, 48,49 as well as other factors such as anxiety, 50 have been implicated in preterm births. We have not considered these elements and believe that further examinations are necessary in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The factors affecting preterm births are many, including medical causes. 46,47 In addition, economic and social factors, 48,49 as well as other factors such as anxiety, 50 have been implicated in preterm births. We have not considered these elements and believe that further examinations are necessary in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic factors-educational attainment in particular-are associated with adverse pregnancy outcomes. [1][2][3][4][5] However, it is challenging to modify an individual's level of education, and opportunities to seek education are not equally distributed throughout the population. It is therefore of great importance to identify modifiable risk factors through which the association with educational attainment is mediated.…”
Section: Introductionmentioning
confidence: 99%
“…6 Conventional observational studies have identified some potential mediating pathways, and cardiometabolic risk factors stand out. 1 For instance, prepregnancy body mass index (BMI) and systolic blood pressure (SBP) have been observed to explain most of the association between educational level and gestational hypertension and preeclampsia. 2,3 Smoking has been observed to likely mediate some of the potential association of educational level with preterm birth 7 and low birth weight, 4 but not with the risk of preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews have shown significant socioeconomic disparities in ABOs [ 14 , 15 ]. ABOs are also used as one of the health indicators to measure existing health inequalities [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%